MODALITY ORIENTATION IN OPRAH WINFREY SHOW FINALE - PRICILIA, GABBY MAUREEN (Institut Pendidikan Tapanuli Selatan, 2018)
The objectives of this study are to identify what the orientation of modality used in Oprah Winfrey Show Finale and to describe how the orientation of metaphor of modality are used in Oprah Winfrey Show Finale. The research design used is descriptive qualitative. The data were taken from Oprahâs love letter in Oprah Show Finale. The data were collected by downloading the transcript of Oprahâs love letter from oprah.com. A letter which is named as âA Love Letter To Youâ by Oprah in Oprah Winfrey Show Finale are the data of this research, then the writer classified the data into types of orientations of metaphor of modality, and then drawing conclusion from the text. The result of the research shows that there are four orientations of modality used, they are subjective implicit, objective implicit, subjective explicit, and objective explicit. The ways of using metaphor of modality orientation is by projecting clause and the functions are to emphasize strong belief and create the objectivity.